Differentially expressed plasma protein fractions in workers of dyeing unit at a textile industry and comparable controls (Bangladesh Journal of Scientific and Industrial Research, 2015)
Workers of textile industry are exposed to different hazardous chemicals that cause adverse effects on their health. As variations in plasma proteins are the best indicators of health status of the subjects, hence, we compared plasma protein fractions, resolved by SDS-PAGE of textile dyeing industry workers (n=30) with control subjects (n=30). Proteins were quantified by Total Lab Quant software and analyzed, statistically, by Student t-test. Thirteen protein fractions were detected ranging 250-17kDa. A significant increase in 132 and 53kDa fractions, whereas, a significant decrement in 87 and 66kDa fractions with a highly significant reduction in 112kDa fraction was observed. However, 250, 224, 43, 23, 19 and 17kDa protein fractions did not vary considerably. As some proteins circulate only during particular physiological or pathological circumstances and may serve as biomarkers of anomalies, the altered expressions of these biomolecules observed in textile dyeing industry workers may be strong predictors of different ailments. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22002 Bangladesh J. Sci. Ind. Res. 49(2), 89-94, 2014